2005
DOI: 10.1007/bf03345527
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers in women with a recent history of gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) is a risk factor for both Type 2 diabetes (DM2) and insulin-resistance syndrome (IRS). C-reactive protein (CRP), fibrinogen and leukocyte count are increased in the IRS and predict DM2 and cardiovascular disease (CVD). The chemochine monocyte chemoattractant protein-1 (MCP-1/CCL2) is also elevated in DM2 and CVD. Recent evidence suggests a relation between chronic inflammation and GDM, but post-delivery information on inflammatory markers in these high-risk women is lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 29 publications
9
39
2
Order By: Relevance
“…This contrasts with previous reports where CRP levels have been found to be elevated in diabetic and insulin-resistant individuals (9,10,39,41). However, in the Diabetes Heart Study, there was no difference in CRP levels between type 2 diabetic subjects and their unaffected siblings (42), although a significant relationship was found between BMI and CRP in the same study as in the data reported here.…”
Section: The Contribution Of Adipose Tissue To Adipokine Levelscontrasting
confidence: 99%
“…This contrasts with previous reports where CRP levels have been found to be elevated in diabetic and insulin-resistant individuals (9,10,39,41). However, in the Diabetes Heart Study, there was no difference in CRP levels between type 2 diabetic subjects and their unaffected siblings (42), although a significant relationship was found between BMI and CRP in the same study as in the data reported here.…”
Section: The Contribution Of Adipose Tissue To Adipokine Levelscontrasting
confidence: 99%
“…In fact, both subclinical inflammation and hypoadiponectinaemia may be chronic defects in this patient population, as increased CRP and low adiponectin in the first trimester have each been shown to independently predict the subsequent development of GDM later during pregnancy [22,23]. Moreover, a limited number of studies following pregnancy have also reported increased levels of inflammatory markers and decreased adiponectin in women with a history of GDM [24][25][26]. By documenting their existence both during pregnancy and at 3 months postpartum, the current study supports the potential chronic nature of these defects, and thereby suggests that they may be of pathophysiological relevance to diabetic risk in this patient population.…”
Section: Discussionmentioning
confidence: 95%
“…Average hsCRP and interleukin-6, but not tumor necrosis factor-␣, were higher in a prior GDM group than in control subjects 3 months after delivery in Austria, with or without direct measures of insulin resistance (149). In Italy, hsCRP and fibrinogen concentrations were significantly elevated in women 1-3 years after pregnancy with GDM, even excluding women with IGT (142). Gestational hyperglycemia predicted a high risk of later metabolic syndrome after adjustments for age and prepregnancy BMI in another Italian study (150).…”
Section: Cardiovascular Risks In Women With Priormentioning
confidence: 88%
“…On the other hand, standard lipoprotein concentrations were not different in women with prior GDM compared with control subjects 1-3 years after pregnancy in Italy (142) and in Spain, despite the increased BMI and waist circumference (30). In the latter study, women with IFG had significantly increased odds ratios for obesity and hypertension than the women with postpartum IGT (30).…”
Section: Cardiovascular Risks In Women With Priormentioning
confidence: 99%